\begin{align} \int_{0}^{1}{\ln\left(1 + \phi x^{2}\right) \over 1+x}\,{\rm d}x &= \sum_{\sigma = \pm} \int_{0}^{1}{\ln\left(1 + {\rm i}\,\sigma\,\phi^{1/2}x\right) \over 1 + x}\,{\rm d}x = \sum_{\sigma = \pm} \int_{1}^{2}{\ln\left(1 - {\rm i}\,\sigma\,\phi^{1/2} + {\rm i}\,\sigma\,\phi^{1/2}x\right) \over x}\,{\rm d}x \\[2mm]&= \sum_{\sigma = \pm}\left\lbrack\ln\left(1 - {\rm i}\,\sigma\,\phi^{1/2}\right)\ln\left(2\right) + \int_{1}^{2}{\ln\left(1 - z_{\sigma}x\right) \over x}\,{\rm d}x\right\rbrack \end{align}
donde $\displaystyle{z_{\sigma} \equiv -\,{{\rm i}\,\sigma\,\phi^{1/2} \over 1 - {\rm i}\,\sigma\,\phi^{1/2}}}$
\begin{align} \int_{0}^{1}{\ln\left(1 + \phi x^{2}\right) \over 1+x}\,{\rm d}x &= \ln\left(1 + \phi\right)\ln\left(2\right) + \sum_{\sigma = \pm}\left\lbrack% \int_{0}^{1}{\ln\left(1 - 2z_{\sigma}x\right) \over x}\,{\rm d}x - \int_{0}^{1}{\ln\left(1 - z_{\sigma}x\right) \over x}\,{\rm d}x \right\rbrack \\[2mm]&= \ln\left(1 + \phi\right)\ln\left(2\right) + \sum_{\sigma = \pm}\left\lbrack\vphantom{\Large A}% -{\rm Li_{2}}\left(2z_{\sigma}\right) + {\rm Li_{2}}\left(z_{\sigma}\right) \right\rbrack \\[1cm]& \end{align}
\begin{align} \int_{0}^{1}{\ln\left(1 + \phi x^{2}\right) \over 1+x}\,{\rm d}x &= \ln\left(1 + \phi\right)\ln\left(2\right) + 2\Re\left\lbrack\vphantom{\Large A}% {\rm Li_{2}}\left(z\right) - {\rm Li_{2}}\left(2z\right) \right\rbrack \\[2mm]& \mbox{with}\quad z = -\,{{\rm i}\,\phi^{1/2} \over 1 - {\rm i}\,\phi^{1/2}} \end{align}
Ver http://en.wikipedia.org/wiki/Polylogarithm#Dilogarithm